Zakat rulings on the deceased in Islamic jurisprudence - Jaafar Mohammed Ahmed,; Ahmed Sabti Ahmed, (Islamic Sciences Journal, 2025)
ABSTRACT A person may die suddenly and have not paid zakat. He may have been busy with many tasks and not paid zakat on his wealth, or he may have been preoccupied with illness or other circumstances. This leaves the deceased not absolved of responsibility before Allah Almighty, as zakat is one of the pillars of Islam. If a person dies without paying zakat on his wealth, his heirs must pay it on his behalf, especially if he was not negligent and did not intentionally delay zakat. Paying zakat on behalf of the deceased is an important matter, and Muslims must be aware of its rulings and details. This is due to the prevalence of chaos and sudden death, which is a form of goodness, and believers are commanded to do good deeds that lead to success. It is also considered a form of righteousness towards the deceased, especially if they have left a will for it to be paid on their behalf before their death. In this research, we examine the details of paying zakat on behalf of the deceased, whether they left a will for it to be paid or not. In this research, I followed an analytical approach by presenting the evidence relied upon by jurists in their reasoning. I also used a critical approach, demonstrating the weakness and invalidity of some evidence. To protest, because the evidence is weak or unacceptable. Through studying this research, it became clear that if the deceased did not bequeath zakat on his behalf, the heirs are not obligated to pay it. Some jurists say the deceased was excessive in his wealth, while others say it must be paid from the capital. However, if the deceased bequeathed zakat, the heirs must pay it from their third.